Proteção judicial dos direitos humanos : o sistema interamericano e a eficácia das sentenças da corte interamericana no Brasil - Marinho, Saulo Lopes (2012)
The international protection of human rights is a theme that since the second half of the twentieth century has gained ground in Law studies. Starting on the ideological shift operated after the Second World War, the issue was initially founded in the existence of legal norms that are situated above states, in addition to rescue ethical bases long forgotten by the international law. In this context, it had been developed the so-called International Protection Systems as symbols of these new concern of international society, among which stands out in Brazil the Inter-American System of Human Rights. Its structure has a jurisdictional organ, the Inter-American Court, which acts in the resolution of human rights violations committed by one of the States submitted to it, appearing as ultimate guarantor of human rights in the Americas. The contributions of international protection and specifically of the Inter-American System to Brazil has been positives. It happens that the judgments of the Inter-American Court, although the legal technique gives them binding force and mandatory power, have suffered of a deficit of effectiveness in Brazil, which is revealed in cases that the country has already been convicted. This deficit is linked to lack of awareness Brazilian State regarding the paramount importance of human rights and the absence of coercive ways available to the Court to impose its decisions.